Rasio Panjang Daun Posterior dengan Daun Anterior Katup Mitral pada Gambaran Ekokardiografi sebagai Parameter Sederhana untuk Menentukan Derajat Keparahan Stenosis Mitral - Zunaidi Syahputra; Nizam Zikri Akbar; Andre Pasha Ketaren; Harris Hasan (The Indonesian Heart Association, 2017)
Background: Determining the severity of mitral stenosis is important for both prognostic and therapeutic reasons. TTE is the gold standard method for assessment of severity mitral stenosis by using planimetry and pressure half time (PHT). Planimetry is accurate but highly operator dependent. PHT is affected by changes in preload or left ventricular compliance. In this study, we evaluate the posterior to anterior mitral valve leaflets length ratio as a novel simple parameter that can be used in peripheral by using common ultrasound to assess the severity of MS.Methods: This cross-sectional study involved 75 patients with rheumatic mitral stenosis (MS) who evaluate echocardiography in Adam Malik Hospital . The severity of MS was classified by planimetry and PHT. The posterior to anterior mitral valve leaflets length ratio was obtained by dividing posterior mitral valve leaflet length to anterior mitral valve leaflets length in the parasternal long axis views at the end diastole.Results: Severe (61.3%), moderate (32%), mild (6.7 %) MS. There was a strong correlation with the posterior to anterior mitral valve leaflets length ratio and mitral valve area by planimetry in spearman correlation ( r=0.892, p<0.001). ROC analysis of the posterior to anterior mitral valve leaflets length ratio with cut-off point < 0.68 could predict severe MS with sensitivity of 97%, specificity of 93%, positive predictive value of 96%, LR (+) of 13.85. Intra-observer and intra-observer variability of this parameter was good (Kappa value of 0.760–0.765) and significant (p< 0.001). Goodness of fit test with Hosmer-Lemeshow test showed this parameter fit with the data.Conclusion: The posterior to anterior mitral valve leaflets length ratio<0.68 can be used as a simple parameter in determining the severity of mitral stenosis with high sensitivity and specificity.